Adipocyte Mineralocorticoid Receptor Activation Leads to Metabolic Syndrome and Induction of Prostaglandin D2 Synthase. Issue 1 (July 2015) - Urbanet, Riccardo; Nguyen Dinh Cat, Aurelie; Feraco, Alessandra; Venteclef, Nicolas; El Mogrhabi, Soumaya; Sierra-Ramos, Catalina; Alvarez de la Rosa, Diego; Adler, Gail K.; Quilliot, Didier; Rossignol, Patrick; Fallo, Francesco; Touyz, Rhian M.; et al.
<x xml:space="preserve">Abstract</x> Metabolic syndrome is a major risk factor for the development of diabetes mellitus and cardiovascular diseases. Pharmacological antagonism of the mineralocorticoid receptor (MR), a ligand-activated transcription factor, limits metabolic syndrome in preclinical models, but mechanistic studies are lacking to delineate the role of MR activation in adipose tissue. In this study, we report that MR expression is increased in visceral adipose tissue in a preclinical mouse model of metabolic syndrome and in obese patients. In vivo conditional upregulation of MR in mouse adipocytes led to increased weight and fat mass, insulin resistance, and metabolic syndrome features without affecting blood pressure. We identified prostaglandin D2 synthase as a novel MR target gene in adipocytes and AT56, a specific inhibitor of prostaglandin D2 synthase enzymatic activity, blunted adipogenic aldosterone effects. Moreover, translational studies showed that expression of MR and prostaglandin D2 synthase is strongly correlated in adipose tissues from obese patients.